Evaluación del comportamiento productivo de cerdos en la etapa de engorde, suplementados con varios niveles de levadura de cerveza (Saccharomyces cerevisiae) - Sánchez Quispe, Dalemberg Gualberto (2020)
In this investigation the productive behavior of pigs in the fattening stage was evaluated, supplemented with various levels of brewer's yeast in order to establish the best level of brewer's yeast (3%, 5%, 7%) in order to determine the Effect of beer yeast levels on weight gain and feed conversion in pig feeding in the fattening stage and perform the economic analysis in the cost / benefit ratio. For this investigation, we worked with a completely randomized block design (DBCA) with 4 treatments and 4 repetitions, with a total of 16 experimental units, Landrace pigs with a live weight of ± 42 Kg at the beginning of the investigation. The experimental results showed that there was a statistical significance (*), in terms of the proposed treatments. Based on the results obtained, we determined that the T3 treatment achieved a greater weight gain reaching a total of ± 39 kg, followed by the T1, T2 and T4 treatments that had a similar productive behavior with a total weight gain of ± 31 kg, the bromatological properties determined by the laboratory analysis indicate that both the commercial balanced diet, and the brewer's yeast supplemented with the animals, meet the nutritional requirements for pigs in the fattening stage, no type was presented of alteration at the renal or hepatic level, since the analysis of the blood biochemistry showed values in range of all the analytes studied, both at the beginning and at the end of the investigation; Regarding the benefit-cost ratio of the T3 treatment, it was the one that presented the best cost-benefit ratio among the treatments with an index of 1.40